Design and evaluation of hospital-based business intelligence system (HBIS): A foundation for design science research methodology. (September 2016) - Kao, Hao-Yun; Yu, Min-Chun; Masud, Mehedi; Wu, Wen-Hsiung; Chen, Li-Ju; Wu, Yen-Chun Jim
Abstract: This paper describes the development of a hospital-based business intelligent system (HBIS) based on a novel developmental methodology, called the design science research methodology (DSRM), and implemented in a regional general hospital in Taiwan. A design science research methodology is adopted to cover six activities: problem identification and motivation, definition of solution objectives, design and development, demonstration, evaluation, and communication. Based on the DSRM developmental method, HBIS was successfully developed and deployed in the hospital case, and a survey of users shows positive results. In addition, the support and involvement of top management in HBIS development is found to be a critical success factor, and system implementation allowed the hospital to significantly improve performance of managerial indicators for the three abovementioned dimensions. This study contributes a novel developmental methodology from the Information Systems (IS) field as a reference model for future HBIS development, along with the integration of indicators from three major managerial dimensions - NHI, hospital accreditation, and healthcare quality. Highlights: A hospital-based business intelligent system (HBIS) is presented. Reporting the development and assessment of a HBIS system. Identifying the critical factors to the development of HBIS. Proposing tools that improve the decision-making of health system administrators.